Myths and misconceptions about parenting and child development among social intervention professionals - Barreto-Zarza, Florencia; Unibaso-Markaida, Iratxe; Díaz-Argüello, Adriana; San Martin Cabezón, Carmen; Arranz, Enrique Bernardino (Anales de Psicología / Annals of Psychology, 2026)
Messages about parenting that lack any scientific basis have become very popular on the social media. It is crucial (I) to analyse the presence of myths about parenting and child development to identify training needs among a sample of family intervention practitioners; (II) to carry out an assessment of myths and misconceptions about parenting and child development using the Questionnaire for Family Assessment of Myths (Q-FAM), as a preventive screening tool for healthy parenting. 1279 practitioners working with families and children aged 0-6 years in various territorial assemblies of the Spanish Red Cross. Participants completed the 32-item Q-FAM online. A descriptive analysis of the presence of myths and misconceptions was carried out and exploratory and confirmatory factor analyses were conducted. The exploratory and confirmatory factor analyses revealed a single-factor model, thereby demonstrating the one-dimensionality of the Q-FAM. The instrument was found to have good psychometric properties, with adequate internal consistency indexes (KR-20 = .860; ω = .872). Results showed the presence of myths and misconceptions regarding issues about overprotection, screens contact, cognitive development, breast feeding, co-sleeping, etc. The Q-FAM also provides empirical support for establishing political targets and actions in the field of positive parenting interventions.